Social franchising as rural entrepreneurial ecosystem development: The case of Krishi Utsho in Bangladesh. (February 2017) - McKague, Kevin; Wong, Jennifer; Siddiquee, Nurul
This study explores the potential of social franchising to contribute to the development of the rural entrepreneurial ecosystem in contexts of market and governance failure in least developed countries. Social franchising is a social enterprise business model that provides market coordination and support systems to rural enterprises so they can achieve social objectives in a financially sustainable way. The case of Krishi Utsho—a network of 112 agricultural input shops in Bangladesh—illustrates how social franchising can address market and government coordination failures in the entrepreneurial ecosystem to benefit both rural entrepreneurs and their client smallholder farming families who earn under US1 per day.